2021
DOI: 10.1002/hbm.25562
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related and individual variations in altered prefrontal and cerebellar connectivity associated with the tendency of developing internet addiction

Abstract: Internet addiction refers to problematic patterns of internet use that continually alter the neural organization and brain networks that control impulsive behaviors and inhibitory functions. Individuals with elevated tendencies to develop internet addiction represent the transition between healthy and clinical conditions and may progress to behavioral addictive disorders. In this network neuroscience study, we used resting‐state functional magnetic resonance imaging (rs‐fMRI) to examine how and whether individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
(79 reference statements)
1
17
0
Order By: Relevance
“…With respect to the possible role of the lingual gyrus (BA18) in excessive smartphone use, a previous investigation has demonstrated that not only does the area receive information from the primary visual cortex but it also affects the cortical endophenotypes for anxiety and depression [ 50 ] which are common emotional comorbidities related to problematic smartphone use [ 7 , 45 ]. Consistent with the function of automatic emotion regulation of the cerebellum [ 49 ] as well as the role of the lingual gyrus (BA18) in modulating both voluntary and automatic emotions [ 50 ], a previous clinical trial has shown that the middle frontal gyrus (BA46) is also responsible for voluntary and automatic emotion control [ 51 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…With respect to the possible role of the lingual gyrus (BA18) in excessive smartphone use, a previous investigation has demonstrated that not only does the area receive information from the primary visual cortex but it also affects the cortical endophenotypes for anxiety and depression [ 50 ] which are common emotional comorbidities related to problematic smartphone use [ 7 , 45 ]. Consistent with the function of automatic emotion regulation of the cerebellum [ 49 ] as well as the role of the lingual gyrus (BA18) in modulating both voluntary and automatic emotions [ 50 ], a previous clinical trial has shown that the middle frontal gyrus (BA46) is also responsible for voluntary and automatic emotion control [ 51 ].…”
Section: Discussionmentioning
confidence: 84%
“…Our ALE results revealed an association between excessive smartphone use and activation of several brain areas, namely the right posterior lobe of cerebellum, the right lingual gyrus (BA18), and the left middle frontal gyrus (BA46) ( Figure 4 and Table 4 ). Regarding the relationship between the cerebellum and behavioral addiction, a previous observational study has reported a disruption of executive-cerebellar networks but increased occipital-putamen connectivity in internet addicts, probably resulting from addiction-sensitive cognitive control processes and bottom-up sensory plasticity [ 49 ]. With respect to the possible role of the lingual gyrus (BA18) in excessive smartphone use, a previous investigation has demonstrated that not only does the area receive information from the primary visual cortex but it also affects the cortical endophenotypes for anxiety and depression [ 50 ] which are common emotional comorbidities related to problematic smartphone use [ 7 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, functional and structural abnormalities of the cerebellum have been linked with IA disorder 48,57 and IAT in healthy adults 12,13 . Patil and colleagues found that reduced spontaneous neuronal activity in the cerebellum was associated with a tendency of developing IA in healthy subjects 12 . A recent structural MRI study showed that the cerebellar volume was negatively correlated with IAT in healthy individuals 13 .…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Patil and colleagues found that reduced spontaneous neuronal activity in the cerebellum was associated with a tendency of developing IA in healthy subjects. 12 A recent structural MRI study showed that the cerebellar volume was negatively correlated with IAT in healthy individuals. 13 The current result extended the previous finding by showing that there was a negative relationship between IAT scores and cerebellar volume in individuals with lower resting RMSSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation